2015
DOI: 10.1021/acs.langmuir.5b02198
|View full text |Cite
|
Sign up to set email alerts
|

A Combined SAXS/SANS Study for the in Situ Characterization of Ligand Shells on Small Nanoparticles: The Case of ZnO

Abstract: ZnO nanoparticles (NPs) have great potential for their use in, e.g., thin film solar cells due to their electro-optical properties adjustable on the nanoscale. Therefore, the production of well-defined NPs is of major interest. For a targeted production process, the knowledge of the stabilization layer of the NPs during and after their formation is of particular importance. For the study of the stabilizer layer of ZnO NPs prepared in a wet chemical synthesis from zinc acetate, only ex situ studies have been pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 37 publications
2
46
0
Order By: Relevance
“…34 Moreover, small-angle X-ray (SAXS) and small-angle neutron scattering (SANS) studies conducted in cooperation with the Chair for Crystallography and Structural Physics at FAU also showed that scattering data for ZnO colloids can only be well fitted when assuming polydisperse spherical NPs. 17, 35 In contrast, data could not be fitted when using models for shape anisotropic NPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Moreover, small-angle X-ray (SAXS) and small-angle neutron scattering (SANS) studies conducted in cooperation with the Chair for Crystallography and Structural Physics at FAU also showed that scattering data for ZnO colloids can only be well fitted when assuming polydisperse spherical NPs. 17, 35 In contrast, data could not be fitted when using models for shape anisotropic NPs.…”
Section: Resultsmentioning
confidence: 99%
“…A combined SANS/SAXS study revealed slightly larger shell thicknesses reaching from 0.7 nm to 1.3 nm. 35 In contrast to AUC, the shell thickness provided by SANS/SAXS is not derived from the hydrodynamic properties of the NP but it describes the native stabilizing layer of the NPs and how far it extends into the dispersion medium. Thus, also acetate molecules exceeding the shear plane of the NP are considered by SANS/SAXS, which is the reason why slightly larger values in case of scattering methods are clearly expected.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] Ak ey role in advancing ZnO NCs has been playedb yt he classical sol-gelm ethodology, [7,8] providing accesst oamultitude of tailoredZ nO nanostructures. Moreover,i nadequate controlo ver the nucleation and growth of quantum-sized ZnO NCs causes low reproducibility and lacking uniformity of the composition of the inorganic core/organics hell interface of the particles, which are associatedw ith ac orrugated surface structure, instability, and permeability of the "swollen" organic coating [10] (Scheme 1). Moreover,i nadequate controlo ver the nucleation and growth of quantum-sized ZnO NCs causes low reproducibility and lacking uniformity of the composition of the inorganic core/organics hell interface of the particles, which are associatedw ith ac orrugated surface structure, instability, and permeability of the "swollen" organic coating [10] (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The very dynamic nature of the NC surface and the strong interplay between capping ligands and the inorganic core [16] are also likely important factors determining charge carrier trapping. Unfortunately, the organic surface ligands are invisible in electron microscopy and can currently be investigated only on the ensemble level using infrared absorption [249, 265, 266], nuclear magnetic resonance spectroscopy [249, 267, 268], or neutron scattering [269, 270]. …”
Section: Excited-state Dynamics In Semiconductor Nanocrystalsmentioning
confidence: 99%